2017
DOI: 10.1021/acs.langmuir.7b02277
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Structure and Stability of Transmembrane Oligomeric Intermediates of an α-Helical Toxin

Abstract: Protein membrane interactions play an important role in our understanding of diverse phenomena ranging from membrane-assisted protein aggregation to oligomerization and folding. Pore-forming toxins (PFTs) are the primary vehicle for infection by several strains of bacteria. These proteins which are expressed in a water-soluble form (monomers) bind to the target membrane and conformationally transform (protomers) and self-assemble to form a multimer transmembrane pore complex through a process of oligomerizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 89 publications
1
51
0
Order By: Relevance
“…In recent molecular dynamics simulations of ClyA, carried out in our laboratory we have shown that membrane inserted arcs or pores are lined by the protein on one face with toroidal lipids forming the pore interior in regions where proteins are absent. 31 These arcs were found to be stable structures with a water channel capable of transporting material across the transmembrane channel supporting the prediction that arcs play a dominant role in the leakage. Arc-like transmembrane constructs have been purported to exist for other a-helical transmembrane proteins such as actinoporins.…”
Section: Inuence Of Conformation and Oligomerization Times A Csupporting
confidence: 66%
“…In recent molecular dynamics simulations of ClyA, carried out in our laboratory we have shown that membrane inserted arcs or pores are lined by the protein on one face with toroidal lipids forming the pore interior in regions where proteins are absent. 31 These arcs were found to be stable structures with a water channel capable of transporting material across the transmembrane channel supporting the prediction that arcs play a dominant role in the leakage. Arc-like transmembrane constructs have been purported to exist for other a-helical transmembrane proteins such as actinoporins.…”
Section: Inuence Of Conformation and Oligomerization Times A Csupporting
confidence: 66%
“…26 Disordered N-terminal residues 1-7 and the C-terminal residues 293-303 unresolved in the crystal structure are important for lytic activity [27][28][29] and hence were modeled using the I-TASSER web server 30,31 as described previously. 29,32 The heptameric crystal structure of the α-hemolysin (AHL) pore (PDB ID 7AHL) 33 has multiple residues with missing co-ordinates (arginine 66 and lysine 70 in chain A, lysine 30 and lysine 240 in chain D, lysine 283 in chain F and lysine 30 in chain G). The missing atoms in these residue side chains were reconstructed using VMD 1.9.1 34 similar to a previous study.…”
Section: Molecular Modelling Of the Clya And Ahl Poresmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations offer a promising alternative to resolve pore formation at the molecular scale. Previous MD simulations of αand β-PFTs (20)(21)(22)(23)(24)(25) were limited to either protein monomers or small oligomers. Simple rate models for the assembly and insertion process have been proposed (26,27), but the role of lipids and the process of pore opening have not been studied in detail.…”
mentioning
confidence: 99%